2022
DOI: 10.1101/2022.09.09.507263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

iPSC-derived astrocytes to model phenotype-specific differential neuroinflammatory and metabolic responses in X-linked adrenoleukodystrophy

Abstract: Objective: The role of astrocytes largely remains to be explored in X-linked adrenoleukodystrophy (X-ALD). Due to limited study models and inaccessibility to patient-tissue samples, we differentiated astrocytes from patient fibroblast-derived induced pluripotent stem cell (iPSCs) which provided a unique system to investigate molecular and etiopathogenetic mechanisms, identify targets, and develop therapeutic agents for X-ALD. Methods: We reprogrammed fibroblasts from adrenomyeloneuropathy (AMN) and cerebral ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 70 publications
3
9
0
Order By: Relevance
“…In the present study, we generated and characterized astrocytes obtained from iPSC lines reprogrammed from skin fibroblasts of additional two male patients each of CTL, AMN and cALD phenotype. In line with our recent report [17], ABCD1 mutation did not affect the reprogramming ability of AMN and cALD skin fibroblasts and the iPSC-lines were successfully differentiated into astrocytes. Immunocytochemical expression analysis of differentiated astrocytes indicated that they were positive for mature astrocyte markers including GFAP, EAAT, S100β and ALD1H1 consistent with previous studies [17,22].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, we generated and characterized astrocytes obtained from iPSC lines reprogrammed from skin fibroblasts of additional two male patients each of CTL, AMN and cALD phenotype. In line with our recent report [17], ABCD1 mutation did not affect the reprogramming ability of AMN and cALD skin fibroblasts and the iPSC-lines were successfully differentiated into astrocytes. Immunocytochemical expression analysis of differentiated astrocytes indicated that they were positive for mature astrocyte markers including GFAP, EAAT, S100β and ALD1H1 consistent with previous studies [17,22].…”
Section: Discussionsupporting
confidence: 90%
“…However, they are unable to account for the differential response seen in AMN and cALD phenotype. We recently documented differential accumulation of VLCFA in patient iPSC-derived astrocytes from AMN and cALD phenotypes [17]. In line with these, VLCFA levels were also differentially increased in AMN and cALD patient iPSC-derived astrocytes in the present study with higher accumulation in cALD patient iPSC-derived astrocytes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations